Immobilized Lipase Catalysed Esterification Of Formic Acid And Methanol - Ali, Maisara Adleena Mohd (Universiti Sains Malaysia, 2022)
Methyl formate is the simplest ester with various uses in industrial applications. Fischer esterification is a conventional esterification that uses acid catalysts, giving drawbacks such as environmental issues. The utilization of biocatalyst is an alternative method for esterification reaction, which provides better sustainability and eco-friendly aspect. This thesis describes the optimization of enzymatic esterification by using the OFAT technique. The reaction of enzymatic esterification involved formic acid and methanol catalyzed by immobilized Candida rugosa lipase in n-hexane solvent to produce methyl formate. 62.24 U/mg of free C. rugosa lipase was immobilized by physical adsorption on Celite 545 support, which resulted in 50 U/mg support in a specific activity. The effect of reaction time, enzyme loading and substrate molar ratio were studied. The highest conversion of 30.22% was obtained at 40°C, with a 1:4 molar ratio of formic acid to methanol, 4 g/L of enzyme loading with an agitation speed of 150 rpm in 1.5mL n-hexane for 60 minutes reaction. Secondary data from the research article was used to study and compare the kinetic model via non-linear regression analysis through rate equation. The best fit with the experimental data was Ping Pong Bi-Bi with inhibition by both substrates with an R2 value of 0.98. The kinetic parameter obtained were, Vmax= 5.98 mmol/min/g, KmM = 0.24 mmol, KmO = 1.16 mmol, KiO = 0.68 mmol and KiM = 0.19 mmol.